Diversity of Orchids (Orchidaceae) in Bonjol Subdistrict, West Sumatra - Yulia Indriani; Elfrida; Ekariana S Pandia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Bonjol District, West Sumatra has a very high diversity of flora, one of the flora found in Bonjol District is orchids (Orchidaceae). However, there is no data that explains the diversity of orchid plants in Bonjol District, so researchers are interested in using this as research. This research aims to find out what types of orchids are found in Bonjol District, the diversity index of orchid plants (Orchidaceae) and the dominance index of the most dominant orchid plants in Bonjol District, West Sumatra. The research was carried out using an exploratory method with direct observation of orchid plants in the field. The sampling method used was purposive sampling, namely taking samples with certain considerations. Sampling was carried out at 2 stations, namely residential areas and forests. Data analysis used the Shannon-Wiener diversity index. The research results showed that the diversity of orchid species (Orchidaceae) in Bonjol District, West Sumatra was classified as moderate, with a total Shannon-Wiener diversity index H' = 1.4117. In Bonjol District, West Sumatra, there are 31 types of orchids from 17 genera, the most frequently found species are Bulbophyllum gibbosum with 35 individuals, while the species found least frequently are Nervelia crociformis and Eria discolor, each with 2 individuals. Then, in the results of calculating the dominance index value for orchids (Orchidaceae) in Bonjol District, West Sumatra, the result was D= 0.044, which means that no species dominates.